STRESS CORROSION CRACKING IN CONSTRUCTION STEEL USING NACL SOLUTION - Gita, I Wayan Ekagra Mana Krsna; Dharmadi , Djarot B.; Sugiarto, Sugiarto (International Journal of Mechanical Engineering Technologies and Applications, 2026)
Corrosive environments can accelerate the degradation of steel materials through various mechanisms, one of which is corrosion. Corrosion is a chemical process that involves the interaction between metals and environmental elements, such as oxygen, water, and salts, leading to degradation of the material. One particularly detrimental form of damage to construction steel is Stress Corrosion Cracking (SCC). A specimen with an initial crack, either existing or pre-engineered, is subjected to constant stress under dissolved conditions in a corrosion environment.  Subsequently, the initial crack in the specimen will propagate until the appearance of a fracture. The SCC process begins with tensile stresses resulting from the load applied to the material. The specimen that has the highest fracture time is GTAW welding with PWHT treatment with a time of 65.33 minutes. The PWHT process has an impact on the length of fracture time on the SCC test specimen.